The Importance of Student-Teacher Relationship in Romanian SEN Schools Among Hungarian Minorities - Dan, Beata Andrea (Central European Journal of Educational Research, 2023)
The research aims to investigate the status of special schools in Romania, with a focus on student-teacher relationships, attachment-based education, and the Hungarian minority. After a brief historical overview of special schools, the study covers two main directions. We start by outlining how special schools view the value of attachment-based education and sheltered workshop conditions. Then we will use quantitative methods to analyze the research findings of a pilot study with a sample of a total of 60. Our focus will be on children with special educational needs. We will emphasize the impact of segregated education processes and examine current practices and rights. Based on the findings of the study, educators who work in SEN schools have better knowledge of their students’ attachment patterns. These educators are responsible for teaching students with SEN and building safe attachments plays a crucial role in the educational process. Special education setting places great importance on fostering secure attachment in students.